Kajian Pengawasan Manajemen Hak Merek pada Endank Soekamti - Sari Pertiwi; Willy Lontoh (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to examine the management of Endank Soekamti's trademark rights, especially at the supervision stage carried out by Endank Soekamti musicians directly. This study applies a qualitative method. The results of the study indicate that the review process applies general management theory presented by Terry & Rue as its main foundation. This theory briefly explains that well-functioning management can be reviewed from the application of 3 main functions of management, namely planning, organizing, and supervision. This study only uses the supervision function as the basis for formulating questions. The limitations on the questions are set so that this study can find out the steps that have been implemented by Endank Soekamti musicians in responding to cases of Endank Soekamti trademark infringement that have occurred. In order to find out the supervision stage implemented by Endank Soekamti musicians. This study concludes that the form of supervision implemented by Endank Soekamti musicians tends to be flexible and applies different follow-up actions to the form of trademark infringement experienced. Keywords: Endank Soekamti, Management, Supervision, Trademark Rights.